Pengaruh Jogging Terhadap Kadar Gula Darah Puasa pada Penderita Diabetes Mellitus Tipe 2 - Santoso S. Kep., Ners M. Kep, Mochamad Budi; Irianto, Gunawan; Erik Tania, Yolanda (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2022)
Background: Diabetes mellitus is a global public health problem. In Indonesia, the prevalence of diabetes mellitus is ranked 6th in the world after China, India, the United States, Brazil and Mexico, which is 10.3 million people (International Diabetes Federation, 2017). One of the pillars of diabetes mellitus is physical activity (sports) including jogging which has a very important role in controlling blood sugar levels. The purpose of this study was to determine the effect of physical exercise jogging on fasting blood sugar levels in pre-elderly people with Type 2 Diabetes Mellitus. Method: This study uses a